Gambaran Pengetahuan Gizi pada Ibu Hamil dalam Pencegahan Stunting di Puskesmas Padalarang Tahun 2023 - Rayhana Azkiya; Shellita Melanie Astuti Setiawan; Gianita Yulia Lestari (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting is a condition where a child's height is less than normal based on age and gender. This occurs due to a lack of good nutritional intake and usually causes various bad health outcomes such as the child's height or body length being shorter than the standard for children his age impaired cognitive development, and a weakened immune system. To get a broad picture of how nutritional knowledge among pregnant women can prevent stunting in the Padalarang Community Health Center coverage area in 2023. In this research, the researcher carried out descriptive research which used a cross-sectional research design by observing and then analyzing the data that had been collected at the time of the study of the sample population, namely pregnant women through the research group. Based on data from the Indonesian Nutrition Status Survey (SSGI), in 2021-2022 there was a decrease in stunting cases from 24.4% to 21.6%, which is calculated to be a 2.8% reduction in stunting cases. Among them, the prevalence of stunting in toddlers (height according to age) based on data from West Bandung Regency is 27.3%. Apart from that, based on data held by the Padalarang Health Center as of 2023, 145 children with stunting came from the villages/districts of Laksanamekar, Cipeundeuy, Kertajawa, and Kertamulya. There were 145 cases of children affected by stunting. Balanced nutrition in pregnant women is a state of balance between the nutrition needed by pregnant women for maternal health and the growth and development of the fetus which can be fulfilled by nutritional intake from a variety of foods. That from the Ulmulr group, the majority of respondents were 20-35 years old, 69 people (71.1%). The majority of the domestic workers (IRTS) did 88 people (90.7%). The majority of the respondents' most recent education was SMA, amounting to 47 people (48.5%). The majority of Trimelstelr 3 pregnancy ulcers were 34 people (35.1%). The majority of the respondents' income was 1 – 5 million rupiah for 52 people (53.6%). The majority of respondents' nutrition knowledge was good, namely 58 people (59.8%). The majority of people involved in Culkulp's prevention of stunting are 65 people (67.0%). Keywords: Stunting, Balanced Nutrition, Cleanliness and Health   ABSTRAK Stunting merupakan suatu kondisi dimana tinggi badan seorang anak yang kurang dari normal berdasarkan usia dan jenis kelamin.hal ini terjadi karena kurangnya konsumsi gizi yang baik dan biasanya menimbulkan bermacam hasil kesehatan yang buruk seperti tinggi atau panjang badan anak lebih pendek dari standar anak seumurannya, gangguan perkembangan kognitif, dan sistem kekebalan tubuh yang melemah. Untuk mengetahui gambaran secara luas mengenai bagaimana pengetahuan gizi pada ibu hamil dalam pencegahan stunting di wilayah cakupan Puskesmas Padalarang pada tahun 2023. Dalam pelnellitian ini, pelnelliti melnggulnakan pelnellitian delskriptif yang melnggulnakan delsain pelnellitian cross selctional delngan melngobselrvasi lalul melnganalisis data yang tellah dikulmpullkan pada waktul telrtelntul sellulrulh popullasi sampell yaitul ibul hamil mellaluli kulelsionelr. Berdasarkan data hasil Survei Status Gizi Indonesia (SSGI), pada tahun 2021-2022 mengalami penurunan kasus stunting dari 24,4% menjadi 21,6% yang terhitung menajdi 2,8% hasil penuruna kasus pada stunting. Diantaranya Pravelansi balita stunting (tinggi badan menurut umur) berdasarkan data Kabupaten Bandung barat 27,3%. Selain itu, berdasarkan data yang dimiliki oleh Puskesmas Padalarang per tahun 2023 anak dengan stunting yang berasal dari Desa/Kelurahan Laksanamekar, Cipeundeuy, Kertajawa, dan Kertamulya kasus yang tercatat sebanyak 145 anak terdampak stunting. Gizi seimbang pada ibu hamil adalah keadaan keseimbangan antara gizi yang diperlukan oleh ibu hamil untuk kesehatan ibu dan tumbuh kembang janinnya yang dapat dipenuhi oleh asupan gizi dari aneka ragam makanan. Bahwa dari segi umur mayoritas responden berumur 20-35 sebanyak 69 orang (71,1%). Pekerjaan responden mayoritas IRT sebanyak 88 orang (90,7 %). Pendidikan terakhir responden mayoritas SMA sebanyak 47 orang (48,5 %). Usia kehamilan responden mayoritas Trimester 3 sebanyak 34 orang (35,1 %). Pendapatan responden mayoritas 1 – 5 juta rupiah sebanyak 52 orang (53,6 %). Mayoritas pengetahulan gizi responden Baik yaitu 58 orang (59,8%). Mayoritas pengetahuan pencegahan stunting responden Cukup yaitu 65 orang (67,0%). Kata Kunci: Stunting, Gizi Seimbang, Kebersihan dan Kesehatan